História, memória e identidade: a utilização de imagens em rede social e na sala de aula - BRAGA, Cristiano Marinho (2021)
This scientific work aims to demonstrate the History, Memory and Identity of the city of Carolina/MA, from the use of images in social network and in the classroom with analysis of historical images of the place, in the preservation and maintenance of History, of the memory and local identity. We seek to rescue the elements that make up the memory of this location to reconstruct and re-signify its local and regional identities from a look at its own history, and with images that represent it. Thus, we understand the senses, feelings and meanings that these images arouse and represent for the subjects of the community in general. The dissertation research was developed in stages and qualitatively, using document analysis and online and face to-face conversations with students from the 8th and 9th grades of Colégio Santa Cruz, Carolina Unit/MA, and with people from the community in general with whom we kept in touch from an Instagram profile, @imagens_quecontamhistória a primordial tool in this process, through which we were able to make images of the place available and learn about what the images aroused from memories and feelings in those who saw them. A challenging and at the same time complex research due to its transformations throughout the pandemic process and the most different feelings awakened, it presents great concepts such as History, memory and identity, with important authors of world historiography, at the same time as brings up discussions about regional and local history, where we also show local authors and writers who in their way brighten the text with their picturesque and interesting stories about Carolina from its beginnings to the present, presenting Carolina that delights the eyes of visitors with its beauties natural, history and culture. It also brings, as one of the guiding themes in this writing and research process, the teaching of History in basic education from a new approach through the use of historical images of the place, first, presented in the aforementioned @Instagram profile, and then later, these with the same images, we held conversation circles with the aforementioned groups online and in person. We understand the difficulties of the moment we have spent in our country in the last two years, we also understand the so-called normal difficulties in the process of developing a master's research, however, we cut ourselves off, just like any other educator and researcher who believes in an education that transforms and liberates that learning History through the elements that make up local and regional History is of paramount importance for a process of knowledge of oneself and the space in which we live and will certainly mark a meeting point for memories from then.